Factibilidad para la implementación de una empresa productora y comercializadora de bocadillo de quesillo y dulce, en el cantón Gonzanamá, provincia de Loja - Ojeda Riatigui, José Vicente (2023)
The purpose of this research is to determine the financial viability of the project through the development of market, technical, organizational, and financial studies, followed by the calculation of financial indicators such as Net Present Value (NPV). The NPV value is $136,630.30, indicating that implementing the present project is viable. The Internal Rate of Return (IRR) is 77.97%, which is higher than the project's opportunity cost, demonstrating a favorable Additionally, we have the fourth indicator, the Payback Period (PP), which relates to the time it takes result. The calculation of the Benefit-Cost Ratio (BCR), which indicates the profit value per dollar invested, is 46 cents, meaning that the project will have a good performance. to recover the investment. In this case, the investment will be recovered in 1 year, 3 months, and 18 days from the start-up of the company. Furthermore, a sensitivity analysis is conducted with a 4.4% increase in costs, resulting in a sensitivity of 0.99, and a 4.4% decrease in revenue, also with a sensitivity of 0.99. After analyzing all the financial indicators and sensitivity measures, it can be concluded that the project titled "Feasibility for the implementation of a company for the production and commercialization of cheese and sweet snacks in the Gonzanama district" is feasible for implementation.